On The Semantic Classifications of Balinese Adverbial Clause - Ketut Widya Purnawati, Ketut Artawa, Made Sri Satyawati (Opción, 1970)
The aim of this research is to describe the adverbial clause marking strategy in Balinese. The data sources of this reasearch are narrative texts in weekly Balinese Newspaper, Bali Orti, and several short stories which are written in Balinese. Each semantic function has at least two different markers, one is for a low register and the other one for a high register. The result showed that adverbial clauses in Balinese can be classified into eleven semantic functions. Each of those semantic functions at least has two different markers for the same semantic function.